Lithuania’s Liberation Movement in the West in the Seventh Decade of the 20th Century: A New Generation Came Forth - Banionis, Juozas (Genocidas ir rezistencija, 2009)
The article reviews the political activities of the main Lithuanian liberation organisations in the West in the 1960s – the Lithuanian American Council, the Supreme Committee for the Liberation of Lithuania, the Committee for a Free Lithuania, and the Lithuanian World Community. During this period, relations between the West and the East softened and the status quo seemed to be settling in Eastern Europe. However, the Lithuanian diaspora, the free Lithuanian people, continued to strengthen the movement for the liberation of Lithuania by uniting the political forces of all the Baltic diaspora through concrete actions.
Keywords: Lithuanian occupation; emigree; emigree organizations; Lithuanian liberation movement